Bloso Fish (Glossogobius giuris sp.) Biscuit in Increasing Albumin Levels in Tuberculosis Patients - M. Choiroel Anwar; Aris Santjaka; Fauzan Makruf (Jurnal Kesehatan Masyarakat, 2025)
Tuberculosis is a major global health threat. Tuberculosis patients frequently suffer hypoalbuminemia. Protein-rich foods like Bloso fish (Glossogobius giuris sp.) can improve patient outcomes by elevating albumin levels and nutritional status. This study aims to evaluate the impact of Bloso biscuit on albumin levels in Tuberculosis patients. This study used a cross-over randomized controlled trial design. Sixty participants were divided into two groups: the treatment group consuming Bloso biscuits and the control group consuming non-Bloso biscuits. Each group was monitored for four weeks, and albumin levels were checked before and after biscuit administration. The formula consists of 15% bloso fish flour, 35% low protein flour, 20% margarine, 7% butter, 10% cheese, 8% egg yolk, 3% cornstarch, and 1% sugar. The study statistically analyzed the albumin level in Tuberculosis patients. This study found that most patients were female (55%) and aged 26-35 (41.7%). The baseline albumin levels in both groups were 4.5 g/dL. The average albumin level in the treatment group increased to 5.07 mg/dL. Based on statistical tests, Bloso fish biscuits significantly increased albumin levels in the treatment group (p<0.05). We concluded that giving Bloso biscuits can increase albumin levels in Tuberculosis patients.